Correction: Adsorption of polycyclic aromatic hydrocarbons over CuZnFeAl–LDH modified by sodium dodecyl sulfate. Issue 49 (8th November 2022) - Liu, Boqing; Cao, Jingjing; Jiang, Yong; Yan, Shichang; He, Haiming; Shi, Yu; Xu, Songsong; Liang, Jinhua; Ren, Xiaoqian
Abstract : Correction for 'Adsorption of polycyclic aromatic hydrocarbons over CuZnFeAl–LDH modified by sodium dodecyl sulfate' by Boqing Liu et al., RSC Adv., 2022, 12, 25623–25632, ; https://doi.org/10.1039/D2RA03968K .